Analisis Perkembangan Asset, DPK, Kredit dan Kapital Bank Perkreditan Rakyat (BPR) SeNusa Tenggara Barat - Hasbullah, Yusuf (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
This research entitled Analysis of Asset Development, DPK, Credit and Rural Bank Credit (BPR) in West Nusa Tenggara. The purpose of this study is to: To know the development of Rural Bank (BPR) in terms of Asset, Third Party Fund (DPK), Credit and Capital in West Nusa Tenggara. According to the level of explanation this type of research includes descriptive research that will describe how the information about society and government on the Development of Rural Banks (BPR) in terms of Asset, Third Party Fund (DPK), Credit and Capital in West Nusa Tenggara. The method used is census, where all the existing BPR in NTB will be verified data that has been updated according to the needs of research and has been published. While the data to be used is secondary data. From the data analysis, 32 (thirty two) Rural Banks (BPR) in West Nusa Tenggara Province found that there are 5 (five) BPRs that have the most Assets from 32 BPRs in West Nusa Tenggara such as: PT. BPR Prima Nadi with Asset 118,626 billion, PT. BPRS Dinar Ashri with 91.957 billion Assets, PD.BPR NTB Sumbawa with Assets 87,096 billion, PD.BPR.Lombok Tengah with 85.451 billion Assets and PT.BPR Samawa Kencana with assets of 81,850 billion. If there are seen in terms of DPK, there are 5 (five) BPRs that can generate funds from 32 BPRs in West Nusa Tenggara such as: PT.BPR.Prima Nadi amounting to 101,191 million, PT.BPR Samawaq Kencana totaling 72.864 million, PT. BPRS Dinar Ashri of 53.517 million, PD.BPR Central Lombok of 50.347 million and PD.BPR.NTB Sumbawa of 47.835 million. In terms of credit, there are 5 (five) BPRs that have distributed the most credit from 32 BPRs in West Nusa Tenggara such as: PT.BPR Prima Nadi of 84,093 million, PD.BPR NTB Central Lombok 80.363 million, PD.BPR NTB Sumbawa amounted to 75,267 million, West Lombok BPR PD of 59.865 million and PT BPR Samawa Kencana totaling 58.653 million.